2011
DOI: 10.4061/2011/230147
|View full text |Cite
|
Sign up to set email alerts
|

Benign Lesions in Mucosa Adjacent to Intestinal-Type Sinonasal Adenocarcinoma

Abstract: Occupational exposure to wood dust is a strong risk factor for the development of intestinal-type sinonasal adenocarcinoma (ITAC); however, knowledge on possible precursor lesions or biomarkers is limited. Fifty-one samples of tumor-adjacent mucosa and 19 control samples of mucosa from the unaffected fossa of ITAC patients were evaluated for histological changes and p53 protein expression. Mild dysplasia was observed in 14%, cuboidal metaplasia in 57%, intestinal metaplasia in 8%, squamous metaplasia in 24%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…IM has been identified near sITAC in persons with wood dust exposure; probably representing a precursor lesion as seen in other cancers (e.g. esophageal carcinoma/Barret's esophagus) [1,5,[9][10][11][12]. A previous study identified IM foci in eight of 42 cases of sITAC with identical TP53 mutations in IM and paired sITAC [9]-in our study, identical pathogenic variants in samples with IM, sITAC and component with HGT present even stronger evidence of this connection.…”
Section: Discussionsupporting
confidence: 71%
“…IM has been identified near sITAC in persons with wood dust exposure; probably representing a precursor lesion as seen in other cancers (e.g. esophageal carcinoma/Barret's esophagus) [1,5,[9][10][11][12]. A previous study identified IM foci in eight of 42 cases of sITAC with identical TP53 mutations in IM and paired sITAC [9]-in our study, identical pathogenic variants in samples with IM, sITAC and component with HGT present even stronger evidence of this connection.…”
Section: Discussionsupporting
confidence: 71%
“…Because the Schneiderian mucosa is of ectodermal origin and normally shows no evidence of intestinal differentiation, ITAC probably develops through intestinal metaplasia induced by hardwood and leather dust. It is hypothesized that normal respiratory mucosa first undergoes cuboidal metaplasia, followed by intestinal metaplasia, and then possibly through dysplasia develops into ITAC . Inhaled wood dust particles larger than 5 μm become entrapped in the mucosa of the middle turbinate and ethmoid and weaken the ciliary function of the nasal cells, which prolongs the contact between the particles with the mucosa …”
Section: Methodsmentioning
confidence: 99%
“…[55][56][57] Finally, foci of intestinal metaplasia of the adjacent sinonasal respiratory epithelium can be detected in about 25% of intestinal-type adenocarcinomas. 58,59 Ancillary Studies.-Ancillary studies are variably needed for the diagnosis of specific entities at this site. For example, NUT carcinoma is recognized by the presence of nuclear protein in testis (NUTM1) gene rearrangement or positivity with the C52 monoclonal antibody against NUT protein.…”
Section: Noncore (Recommended) Elementsmentioning
confidence: 99%